EFFECT OF INCREASING THE FERTILIZER DOSE ON BIOMASS PRODUCTION OF Eucalyptus dunnii Maiden - Dick, Grasiele; Schumacher, Mauro Valdir; Araujo, Elias Frank de (Floresta, 2020)
With the recent expansion of Eucalyptus dunnii Maiden cultivation in central region of Rio Grande do Sul state, recurrent questions arise from both research and operational silviculture, especially in relation to mineral fertilization. The objective of this study was to test the effect of fertilizer dose increase (150, 225 and 450 g plant-1 of N-P2O5-K2O, in 24:00:24 proportion) on the biomass production, carbon stock and nutrients in Eucalyptus dunnii trees cultivated in dystrophic Inceptisol, in central region of Rio Grande do Sul state, Brazil. This study revealed that there is no effect of the fertilizer dose increase on the accumulation of biomass, carbon and nutrients in components of Eucalyptus dunnii trees. The nutrients were more concentrated in leaves; in stemwood there was greater stock of carbon and potassium; in branches and stembark the calcium prevailed. Due to the significant biomass production, regardless of fertilizer dose, aiming at reducing costs and environmental impacts, it is recommended to apply mineral fertilization with 150 g plant-1 of N-P2O5-K2O, in 24:00:24 proportion, in Eucalyptus dunnii stand cultivated in dystrophic Inceptisol, in central region of Rio Grande do Sul state, Brazil.